PROGRAM PEMBERDAYAAN WARGA BINAAN LAPAS II.B KOTAPAREPARE - Patahuddin, Patahuddin; Syawal, Syawal; Akhsan, Akhsan (Jurnal BALIRESO, 2018)
Community Empowerment Program of Lembaga Pemasyarakatan (LAPAS) Class II.B Parepare isa program which aims to improve the skills, talents and professionalism of the prisoner inaccordance with their talents, interests, physical and mental development, and the potential of theirenvironment as a means to work in improving the peoples economy and alleviating poverty aswell as improving the quality of prisonersâ life. Our empowerment program which wasimplemented in the LAPAS class II.B Parepare includes; processing of patchwork, Sewing courseand screen printing. The objectives of the three programs are; 1). As a skill that can provide asource of income as long as they are in LAPAS, 2) To provide additional skills for the prisoners asa provision for entrepreneurship later when they are free from LAPAS. The Implementation ofCommunity Empowerment Program of LAPAS Class II. B Parepare begins with anentrepreneurial Seminar then followed by a patchwork processing training that includes themanufacturing of a doormat and pin point storage, sewing and screen printing courses.